A Luminescent Zinc(II) Metal–Organic Framework for Selective Detection of Nitroaromatics, Fe3+ and CrO42−: A Versatile Threefold Fluorescent Sensor. Issue 8 (21st July 2016) - Li, Bao‐Hong; Wu, Jian; Liu, Jian‐Qiang; Gu, Chu‐Ying; Xu, Jing‐Wen; Luo, Miao‐Miao; Yadav, Reena; Kumar, Abhinav; Batten, Stuart R.
Abstract: A new Zn II metal–organic framework, [Zn6 (L)3 (DMA)4 ]⋅5 DMA (H4 L=[1, 1′:3′, 1′′‐terphenyl]‐3, 3′′, 5, 5′′‐tetracarboxylic acid, DMA=dimethylacetamide), has been synthesized and characterized. The structure contains a three‐dimensional 3, 4, 4, 6‐connected net with (4.6 2 )2 (6 6 )(6 6 )(4 2 .6 10 .8 3 ) topology and displays selective detection of nitrobenzene, CrO4 2− and Fe 3+ ions. The present work thus indicates that this metal–organic framework could be a prospective candidate for developing novel luminescence sensors for the selective sensing of nitrobenzene, which can be used as a precursor for explosives. Furthermore, the photoluminescent properties of this material in different solvents and with various analytes were investigated and corroborated by theoretical calculations. The results were in good agreement with the experimental solvent‐dependent luminescence behavior. Abstract : Explosive‐controlled afterglow : A new Zn metal–organic framework contains two distinct types of pores (A & B) and displays selective detection, through photoluminescence quenching, of nitrobenzene, a precursor for explosives, as well as CrO4 2− and Fe 3+ ions.